2002
DOI: 10.1212/wnl.58.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the fusiform face area impair perception of facial configuration in prosopagnosia

Abstract: Perception of facial configuration is impaired in patients with prosopagnosia whose lesions involve the right fusiform gyrus. This deficit is especially manifest when attention must be distributed across numerous facial elements. It does not occur with more anterior bilateral temporal lesions. Loss of this ability may contribute to the recognition defect in some forms of prosopagnosia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
249
3
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(285 citation statements)
references
References 63 publications
31
249
3
2
Order By: Relevance
“…However, cerebral achromatopsia from lingual and fusiform lesions usually affects hue and saturation discrimination, with preservation of lightness perception [30][31][32]. Indeed, this was the rationale for choosing to modulate lightness rather than color in our paradigm [28]. In prosopagnosic patients, difficulty with perceiving eye lightness is unusual and can be associated with a more general deficit in lightness perception [33] and more extensive collateral damage to peri-striate cortex [28], hence in our aMCI cohort, it is also possible that a deficit in discriminating eye color may indicate more diffuse involvement of visual cortex in addition to fusiform damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, cerebral achromatopsia from lingual and fusiform lesions usually affects hue and saturation discrimination, with preservation of lightness perception [30][31][32]. Indeed, this was the rationale for choosing to modulate lightness rather than color in our paradigm [28]. In prosopagnosic patients, difficulty with perceiving eye lightness is unusual and can be associated with a more general deficit in lightness perception [33] and more extensive collateral damage to peri-striate cortex [28], hence in our aMCI cohort, it is also possible that a deficit in discriminating eye color may indicate more diffuse involvement of visual cortex in addition to fusiform damage.…”
Section: Discussionmentioning
confidence: 99%
“…Functional imaging studies in healthy subjects have identified a fusiform face area (FFA) in the lateral aspect of the fusiform gyrus that is activated more by faces than other objects [24][25][26], and which may be involved in discriminating the structural aspects of faces relevant to facial identity [27]. Prosopagnosic patients with right fusiform lesions are impaired in the perception of facial structure, especially the configuration or spatial arrangement of features within a face [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the ability to configure local elements and face processing is well-established in other populations. There are several studies showing that individuals with prosopagnosia perform poorly on tasks that require the integration of perceptual information (Barton et al, 2002) and integrative agnosic patients who are impaired at grouping information to form a global shape may show concurrent problems in object and face recognition (Behrmann & Kimchi, 2003;Ricci, Vaishnavi, & Chatterjee, 1999). Moreover, individuals who are congenitally prosopagnosic (CP), with no identifiable neural substrate that gives rise to this behavioral alteration, are impaired on the global/local task and show a profile similar to that of the autistic individuals on the very same few/many experiment conducted here (Behrmann et al, 2005).…”
Section: Preference For Local Information In Autismmentioning
confidence: 99%
“…Indeed, individuals with integrative visual agnosia who experience difficulty in deriving configural information, are also impaired both at recognizing known faces and at discriminating novel faces. The reverse finding is also reported: individuals who are impaired at face processing either as a result of a brain damage (acquired prosopagnosia) (Barton, Press, Keenan, & O'Connor, 2002;Behrmann & Kimchi, 2003) or as a result of a congenital problem are also impaired at extracting configurations from local elements (Behrmann et al, in pressBehrmann, Avidan, Marotta, & Kimchi, 2005;Le Grand, Mondloch, Maurer, & Brent, 2004). A further indication of the relationship between faces and configurations comes from comparisons of performance on upright versus inverted faces, relative to objects.…”
Section: Introductionmentioning
confidence: 96%